Small ubiquitin‐like modifier 2 (SUMO2) is critical for memory processes in mice. Issue 11 (10th September 2020) - Yu, Shu; Galeffi, Francesca; Rodriguiz, Ramona M.; Wang, Zhuoran; Shen, Yuntian; Lyu, Jingjun; Li, Ran; Bernstock, Joshua D.; Johnson, Kory R.; Liu, Shuai; Sheng, Huaxin; Turner, Dennis A.; et al.
Abstract: Small ubiquitin‐like modifier (SUMO1‐3) conjugation (SUMOylation), a posttranslational modification, modulates almost all major cellular processes. Mounting evidence indicates that SUMOylation plays a crucial role in maintaining and regulating neural function, and importantly its dysfunction is implicated in cognitive impairment in humans. We have previously shown that simultaneously silencing SUMO1‐3 expression in neurons negatively affects cognitive function. However, the roles of the individual SUMOs in modulating cognition and the mechanisms that link SUMOylation to cognitive processes remain unknown. To address these questions, in this study, we have focused on SUMO2 and generated a new conditional Sumo2 knockout mouse line. We found that conditional deletion of Sumo2 predominantly in forebrain neurons resulted in marked impairments in various cognitive tests, including episodic and fear memory. Our data further suggest that these abnormalities are attributable neither to constitutive changes in gene expression nor to alterations in neuronal morphology, but they involve impairment in dynamic SUMOylation processes associated with synaptic plasticity. Finally, we provide evidence that dysfunction on hippocampal‐based cognitive tasks was associated with a significant deficit in the maintenance of hippocampal long‐term potentiation in Sumo2 knockout mice. Collectively, these data demonstrate that protein conjugation by SUMO2 is critically involved in cognitive processes.